1994
DOI: 10.1111/j.1365-3024.1994.tb00368.x
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic diversity of the asexual developmental stages of Eimeria tenella

Abstract: Total polypeptides from unsporulated and sporulated oocysts, sporozoites and the first two generations of merozoites of Eimeria tenella were fractionated by electrophoresis through polyacrylamide gels. The parasites are complex and the arrays of polypeptides differ for each of the developmental stages indicating that there is stage-specific control of gene expression. In particular, first generation merozoites display a markedly different polypeptide profile to that of either sporozoites or second generation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 17 publications
2
9
0
Order By: Relevance
“…In common with other Eimeria spp., this cycle is complex, consisting of four distinct, sequential, asexual, replicative generations, followed by a sexual phase (see Materials and Methods). Antigenic diversity between the different developmental stages of eiinerian coccidia is well known (Danforth 1989, Tomley 1994, as is their differential capacity for inducing protective immunity (McDonald et al 1988). It is possible that the second peak represents a response to the development of the large gametocytes characteristic of this species, thought to contain protective antigens (Wallach et a f .…”
Section: Discussionmentioning
confidence: 99%
“…In common with other Eimeria spp., this cycle is complex, consisting of four distinct, sequential, asexual, replicative generations, followed by a sexual phase (see Materials and Methods). Antigenic diversity between the different developmental stages of eiinerian coccidia is well known (Danforth 1989, Tomley 1994, as is their differential capacity for inducing protective immunity (McDonald et al 1988). It is possible that the second peak represents a response to the development of the large gametocytes characteristic of this species, thought to contain protective antigens (Wallach et a f .…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA (gDNA) and total RNA were extracted from oocysts using the TRIzol® reagent (Invitrogen, Paisley, UK) as detailed previously (Marugan-Hernandez et al, 2016). Protein extracts from sporozoites and merozoites were obtained following standard procedures (Tomley, 1994).…”
Section: Isolation Of Nucleic Acids and Proteins And Synthesis Of Comentioning
confidence: 99%
“…The antibody responses of chickens to Eimeria infections have been characterized with regard to parasite lifecycle stages, immunodominant antigens and dynamics (Xie et al, 1992;Smith et al, 1993;Tomley, 1994;Talebi and Mulcahy, 1995;Tajima et al, 2003;Onaga et al, 2005;Constantinoiu et al, 2007). However, most studies of the antibody responses reported to date have been conducted with wild-type strains that have not been subject to any selection.…”
Section: Introductionmentioning
confidence: 96%